Identidad cultural y lingüística de estudiantes de educación básica: una revisión sistemática - Carpio-Anyosa, Juan de Dios (2024)
An emotion of identity, expressed in the diversity of cultural manifestations, represents the feeling of belonging to a community or group; This article explores information about the identity reality of basic education students with their cultural and linguistic heritage, and examines proposals developed by researchers to strengthen said identity; The information search was carried out in Google Scholar, Scielo and Dialnet with the descriptor “cultural and linguistic identity of basic education students”; extracting information from the last five years (2019 – 2024), the results of which show that the culture and language of minority communities or human groups are at risk of disappearing, taking with them an entire living culture; In conclusion, to rescue and preserve the hereditary cultural legacy, it is necessary and essential to implement relevant strategies from schools and other institutions.